2015
DOI: 10.1186/s12885-015-1386-7
|View full text |Cite
|
Sign up to set email alerts
|

Variable expression levels of keratin and vimentin reveal differential EMT status of circulating tumor cells and correlation with clinical characteristics and outcome of patients with metastatic breast cancer

Abstract: BackgroundCTCs expressing variable levels of epithelial and mesenchymal markers in breast cancer have previously been reported. However, no information exists for keratin expression levels of CTCs in association with disease status, whereas assays for the characterization of transitional EMT phenotypes of CTCs in breast cancer are rather lacking. We investigated the correlation between keratin expression of CTCs and patients’ outcome and characterized the EMT status of CTCs via the establishment of a numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 19 publications
2
89
0
Order By: Relevance
“…Presence of mesenchymal CTCs was associated with shorter survival in MBC [4] , which was also confirmed using a single CTC analysis approach [44] . MBC patients Whereas epithelial cells seem to be more capable of establishing tumor colonies at distant sites (proliferative phenotype -Ki-67+), mesenchymal cells are more resilient to changing conditions, thus are better equipped to survive during the metastatic cascade.…”
Section: Clinical Significance Of Emt In Ctcsmentioning
confidence: 56%
See 1 more Smart Citation
“…Presence of mesenchymal CTCs was associated with shorter survival in MBC [4] , which was also confirmed using a single CTC analysis approach [44] . MBC patients Whereas epithelial cells seem to be more capable of establishing tumor colonies at distant sites (proliferative phenotype -Ki-67+), mesenchymal cells are more resilient to changing conditions, thus are better equipped to survive during the metastatic cascade.…”
Section: Clinical Significance Of Emt In Ctcsmentioning
confidence: 56%
“…Recently, plastin-3, a specific, novel marker useful for the detection of CTCs undergoing EMT, has been described [42,43] . Also, although with a slight difference, some investigators used a ratio of epithelial and mesenchymal markers to describe CTC phenotypes [19,44] .…”
mentioning
confidence: 99%
“…This observation should be attributed to the finding that, in these particular patients, IF staining could not reveal the presence of either TTF-1 + /EpCAM + or CK + /EpCAM + CTCs since CS recognizes CK + CTCs which are, previously, captured by an anti-EpCAM antibody. It is well known that epithelial tumor cells migrating through the bloodstream undergo EMT which is characterized, among others, by a loss of expression of epithelial markers325455; therefore, it is reasonable to hypothesize that, in this small subgroup of patients without detectable CTCs by CS, the TTF-1 + /EpCAM − CTCs probably represent CTCs undergoing EMT. This is in accordance with studies reporting that the CTC detection rate was higher using EpCAM-independent enrichment methods56.…”
Section: Discussionmentioning
confidence: 99%
“…Markers of EMT in CTCs have the potential to provide both prognostic and predictive information. As discussed above, in breast cancer, the number of mesenchymal CTCs has been linked to disease progression and decreased overall survival (Polioudaki et al, 2015;Yu et al, 2013). In colorectal cancer, a study of CTCs in over a thousand patients found that biphenotypic and mesenchymal CTCs correlated with clinical stage, lymph node, and distant metastases (Zhao et al, 2017).…”
Section: Clinical Implications Of Epithelialto-mesenchymal Transitionmentioning
confidence: 99%